Molecular cytogenetics (London : BioMed Central, 2008)
"Encompasses all aspects of chromosome biology and the application of molecular cytogenetic techniques in all areas of biomedicine."
Articles are added consecutively to the current annual volume and are reflected in the enumeration.
Vol. 1, issue 1 (Dec. 2008); title from journal home page (BioMed Central, viewed Apr. 8, 2008).
Vol. 11, issue 1 (Dec. 2018) (Springer Link website, viewed Apr. 6, 2018).
Keywords: Cytogenetics -- Periodicals; Chromosomes -- Periodicals; Molecular genetics -- Periodicals; Chromosomes; Cytogenetics; Molecular genetics; Cytogenetics; Chromosomes; Biochemical Phenomena; Genetics; Electronic journals